Risk Reduction in Online Flight Reservation: The Role of Information Search - Lee, Kwee-Fah; Haque, Ahasanul; Maulan, Suharni; Abdullah, Kalthom; Tarofder, Kumar (Journal of Reviews on Global Economics, 2018)
The air industry is very competitive. Operating costs are high. To survive and earn profits, it is imperative for airlines to save substantial costs. This can come from selling tickets online. However, in many developing countries including Malaysia, a lot of consumers still refuse to buy flights online. Perceived risk of the internet is a key likely reason. To overcome this resistance, reducing perceived risk is crucial. This study examines the influence of perceived risk and risk-relievers on intention to reserve flight online. The two risk-relievers investigated are information type and personal sources of information. Using data collected online, PLS-SEM analysis was conducted to examine the relationship between type of information, personal sources of information, perceived risk, and intention to reserve flight online. Information type is found to relieve perceived risk and increases online reserve intention. Surprisingly, the results for personal sources of information show otherwise. In addition, perceived risk is empirically supported as being multidimensional. The findings suggest the importance of managing information to relieve risk perceptions so that airlines can stimulate higher online reservations. Thus, better profits can be made in spite of a competitive business environment.